Ethnopharmacology of Pinus species with focus on the Hispaniola pine (Pinus occidentalis Swartz): evidence, gaps, and research roadmap - Núñez-Selles, Alberto J.; Nuevas-Paz, Lauro; Gómez-Torres, Elisa A. (Frontiers in Pharmacology, 2025)
The review systematically maps the ethnomedicinal uses and chemistry of Pinus spp., with an emphasis on the under-studied Pinus occidentalis Swartz, known as “pino criollo”, “pino de cuaba” or “pin creole”. It is the only native pine species of Hispaniola, and holds ecological, cultural, and medicinal significance across the Dominican Republic and Haiti. A data search was conducted across several databases (Google Scholar, SciFinder, Scopus, ScienceDirect, PubMed/Medline, and TRIP) to evaluate the existing knowledge of P. occidentalis spp. and compare it to that of other Pinus species for medicinal uses. The search showed evidence about the medicinal use of this pine species for treating respiratory ailments (cough, cold, and flu), skin infections, wounds, and inflammatory conditions, mainly through hot decoctions of pine needles, bark, cone tender sprouts, and the resin in some locations in Hispaniola. Still, phytochemical data were scarce, limited to the composition of the needle’s essential oil and resin’s turpentine oil in the 20th century. Systematic pharmacological validation of these limited ethnopharmacological findings is still pending, along with the determination of phytochemicals. Research on P. occidentalis shows potential as a natural health product. The urgent need for sustainable strategies is emphasized by conservation concerns related to habitat loss and deforestation. Future research should focus on detailed ethnopharmacology, conservation and propagation techniques for its exploitation, extraction technologies, chemical profiling, and pharmacological screening according to ethnomedicinal surveys, to set P. occidentalis as a promising candidate for phytotherapeutic development and integrative health applications in Hispaniola. These gaps underscore the need for a research roadmap of this endemic tree across the island. The review represents the first comprehensive synthesis of the ethnomedical applications of P. occidentalis Swartz, systematically mapping its cultural and therapeutic significance across Hispaniola.